Development and Evaluation of the Belief Acceptance Scale - Wintering, Nancy A. (Journal of beliefs and values, 2014)
The Belief Acceptance Scale (BAS) is a nine question scale that was developed to evaluate how open and accepting an individual is to other people’s beliefs across interdependent life domains. The purposes of this article are to demonstrate the internal consistency of the BAS and examine the instrument’s substructure and to correlate the BAS with validated measures of religiosity and demographic data gathered from a web-based Survey of Spiritual Experiences. The BAS focuses on cultural beliefs instead of religious motivations and was designed to be administered to religious and non-religious individuals. Three domains of belief acceptance were tested: the internal or subjective openness to other beliefs (Psychological Domain), willingness to participate in other ideologies and rituals (Reciprocal Domain), and the willingness to date or marry outside one’s belief system or cultural background (Social Domain). Responses from 350 individuals were correlated and analysed to estimate the scale’s internal consistency and subscale structure. Analyses support the validity of the BAS scores in that they demonstrate expected correlations with demographic data and standardised measures of religiosity. The results show that the BAS is an internally consistent scale with a coherent substructure that adequately measures openness to other beliefs, ideologies and belief systems.